2016
DOI: 10.1007/s11912-016-0541-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transoral Robotic Surgery in the Management of HPV Negative Oropharyngeal Squamous Cell Carcinoma

Abstract: The incidence of oropharyngeal squamous cell carcinoma (OPSCC) is on the rise. This is largely due to the rapid increase in HPV positive OPSCC, which has been shown to confer a survival advantage. HPV negative OPSCC, however, has a more aggressive tumor biology and is a challenge to treat with standard current therapies. Chemoradiation has demonstrated poor locoregional control in HPV negative OPSCC, and open surgeries are associated with high morbidity. Transoral robotic surgery (TORS) has been proposed as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 52 publications
3
31
0
1
Order By: Relevance
“…Although deintensification is warranted in patients with HPV-positive oropharyngeal SCC with survival rates exceeding 90%, the opposite is true for HPV-negative oropharyngeal SCC, in which intensification may improve the poor prognosis seen in this group. 36 The evidence supporting a treatment paradigm in this select patient population is scarce and relies mostly on small retrospective analyses or subgroup analyses of prospective studies which, in either case, are plagued by the limited sample size of the HPV-negative patient population. 5,21,37,38 For instance, the 2-year survival ranged from 31%-74% in studies using nonsurgical approaches, 5,21 whereas it was 80%-94% in TORS-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although deintensification is warranted in patients with HPV-positive oropharyngeal SCC with survival rates exceeding 90%, the opposite is true for HPV-negative oropharyngeal SCC, in which intensification may improve the poor prognosis seen in this group. 36 The evidence supporting a treatment paradigm in this select patient population is scarce and relies mostly on small retrospective analyses or subgroup analyses of prospective studies which, in either case, are plagued by the limited sample size of the HPV-negative patient population. 5,21,37,38 For instance, the 2-year survival ranged from 31%-74% in studies using nonsurgical approaches, 5,21 whereas it was 80%-94% in TORS-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we argue that definitive surgery be recommended more often for the non‐HPV‐related patient population with poor prognosis because of its potential to increase survival. Robotic surgery was previously proposed for patients with HPV‐negative advanced oropharyngeal cancer in order to improve survival and to reduce surgery‐induced functional impairment …”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery was previously proposed for patients with HPV-negative advanced oropharyngeal cancer in order to improve survival and to reduce surgery-induced functional impairment. 36 For hypopharyngeal cancer, there has similarly been a steady decline in the use of open surgery 37,38 because of the increasing attempts to preserve speech and swallowing function. However, organ-conserving CRT entails significant adverse effects as surgery, with a large number of patients remaining gastrostomy tube-dependent and tracheotomydependent.…”
Section: Discussionmentioning
confidence: 99%
“…A few prospective series have identified that adding surgery to the treatment for patients with HPV-negative cancers offers better control rates [22]. As discussed above, the morbidity and mortality rates attributed to open surgery [1] do not apply to surgical practices in the current day, and especially to transoral surgery; data on 30-day mortality from the UK national head and neck database indicates a mortality of < 1% [23].…”
Section: Non-hpv-related Squamous Cell Cancersmentioning
confidence: 99%